Haplotype association between haptoglobin (Hp2) and Hp promoter SNP (A-61C) may explain previous controversy of haptoglobin and malaria protection. - Sharon E Cox; Conor Doherty; Sarah H Atkinson; Chidi V Nweneka; Anthony J C Fulford; Hala Ghattas; Kirk A Rockett; Dominic P Kwiatkowski; Andrew M Prentice (PLoS ONE)
Background Malaria is one of the strongest recent selective pressures on the human genome, as evidenced by the high levels of varying haemoglobinopathies in human populations-despite the increased risk of mortality in the homozygous states. Previously, functional polymorphisms of Hp, coded by the co-dominant alleles Hp1 and Hp2, have been variously associated with several infectious diseases, including malaria susceptibility. Methodology/principal findings Risk of a clinical malarial episode over the course of a malarial transmission season was assessed using active surveillance in a cohort of Gambian children aged 10-72 months. We report for the first time that the major haplotype for the A-61C mutant allele in the promoter of haptoglobin (Hp)-an acute phase protein that clears haemoglobin released from haemolysis of red cells-is associated with protection from malarial infection in older children, (children aged >or=36 months, >500 parasites/ul and temperature >37.5 degrees C; OR = 0.42; [95% CI 0.24-0.73] p = 0.002) (lr test for interaction, <36 vs >or=36 months, p = 0.014). Protection was also observed using two other definitions, including temperature >37.5 degrees C, dipstick positive, plus clinical judgement of malaria blinded to dipstick result (all ages, OR = 0.48, [95% CI 0.30-0.78] p = 0.003; >or=36 months, OR = 0.31, [95% CI 0.15-0.62] p = 0.001). A similar level of protection was observed for the known protective genetic variant, sickle cell trait (HbAS). Conclusions/significance We propose that previous conflicting results between Hp phenotypes/genotypes and malaria susceptibility may be explained by differing prevalence of the A-61C SNP in the populations studied, which we found to be highly associated with the Hp2 allele. We report the -61C allele to be associated with decreased Hp protein levels (independent of Hp phenotype), confirming in vitro studies. Decreased Hp expression may lead to increased oxidant stress and increased red cell turnover, and facilitate the development of acquired immunity, similar to a mechanism suggested for sickle cell trait.